Development of selection criteria for electric drive crane mechanisms - Герасимяк, Ростислав Павлович; Савич, Светлана Павловна; Шабовта, Михаил Юрьевич (Eastern-European Journal of Enterprise Technologies, 2015)
The paper considers several options of AC drive: traditional with the resistor control, with thyristor voltage converter and with frequency converter, the latter with a resistor braking or energy recovery possibility. An overview of the static and dynamic characteristics of each of the electric drives is proposed, based on which recommendations are made for using an asynchronous electric drive from the proposed options in specific cases. Particular attention should be paid to the energy performance, losses in the motor circuits that need to be calculated for each individual crane mechanism. The proposed recommendations allow the designers of crane mechanisms (lifting, travel, slewing), the personnel operatig them, to consciously choose the electric drive for the designed or reequipped actual cranes operating in specific, well-known conditions. Thus, the cranes will be equipped with the asynchronous electric drive, best for the given conditions.